2018
DOI: 10.1002/cbic.201800130
|View full text |Cite
|
Sign up to set email alerts
|

Similar but Not the Same: First Kinetic and Structural Analyses of a Methanol Dehydrogenase Containing a Europium Ion in the Active Site

Abstract: Since the discovery of the biological relevance of rare earth elements (REEs) for numerous different bacteria, questions concerning the advantages of REEs in the active sites of methanol dehydrogenases (MDHs) over calcium(II) and of why bacteria prefer light REEs have been a subject of debate. Here we report the cultivation and purification of the strictly REE‐dependent methanotrophic bacterium Methylacidiphilum fumariolicum SolV with europium(III), as well as structural and kinetic analyses of the first metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
137
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(156 citation statements)
references
References 64 publications
16
137
0
3
Order By: Relevance
“…This is in line with the findings from as pectrophotometric horse heart cytochrome c assay,w here only in the presence of MDH, methanol, and cytochrome c GJ was the reduction of as econd cytochrome observed. Cyanide has been included in published MDH assays [11] as ap rotective agent to avoid inhibition by the artificial phenazine ethosulfate mediatora th igh concentrations but this was also not required here when the natural electron acceptor cytochrome c GJ was used. + 200 mV) coincides with that of the cytochrome c GJ redox couple indicating that electrocatalysis is mediated by cytochrome c GJ .…”
Section: Methanol Oxidation Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with the findings from as pectrophotometric horse heart cytochrome c assay,w here only in the presence of MDH, methanol, and cytochrome c GJ was the reduction of as econd cytochrome observed. Cyanide has been included in published MDH assays [11] as ap rotective agent to avoid inhibition by the artificial phenazine ethosulfate mediatora th igh concentrations but this was also not required here when the natural electron acceptor cytochrome c GJ was used. + 200 mV) coincides with that of the cytochrome c GJ redox couple indicating that electrocatalysis is mediated by cytochrome c GJ .…”
Section: Methanol Oxidation Catalysismentioning
confidence: 99%
“…[11] The higher K M,app value is ar esult of mass transport limitations of thed ialysis membrane. Upon graduala ddition of methanol, the transformation from aq uasi-reversible transient voltammogram (curve a) through an asymmetric peak-shaped response (curvesb !e) and finally to as igmoidal wave above 50 mm methanoliss een with saturation at 230 mm methanol.…”
Section: Methanol Concentration Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…The first detailed biochemical and structural characterization of a Ln‐dependent MDH was of XoxF from M. fumariolicum , an organism that requires lanthanides for growth, with La–Nd preferred, although Sm, Eu, and Gd can also support weak growth. Further studies demonstrated that this XoxF had maximal activity in the standard artificial dye‐linked assay (Scheme B) when metallated with Pr and Nd. The activity was ≈30 % lower with La and fell off quickly beyond Nd.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the dependence on lanthanides, the only available XoxF structures, those of the Methylacidiphilum ( Ma .) fumariolicum SolV enzyme (SolV-XoxF), reveal Ce(III), La(III), or Eu(III) ions in the active site [12, 18]. …”
Section: Introductionmentioning
confidence: 99%